Expression and Significance of Lipin1 and AMPKα in Hepatic Insulin Resistance in Diet-Induced Insulin Resistance Rats - Chen, S. H.; Zhuang, X. H.; Liu, Y. T.; Sun, A. L.; Chen, C. R. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Lipin1, a lately indentified adipokine, may link obesity with insulin resistance and diabetes. The present study aimed to investigate the changes and significance of lipin1 expression and lipin1-AMPK signaling in diet-induced hepatic insulin resistance.24 4-week-old Male Wistar rats were randomly divided into 2 groups: (1) control group (CO), (2) high-fat diet group (HF). Insulin sensitivity was evaluated by hyperinsulinemic-euglycemic clamp technique. The mRNA levels of α1 and α2 subunit of AMPKα as well as Lipin1 were measured using Real-time RT-PCR. The activities of AMPKα and Akt were evaluated by detection of p-AMPKα (Thr-172) and p-Akt (ser473) by Western blot.After treatment of 4 months, HF group showed significantly increased levels of body weight, fasting plasma glucose and insulin levels; Plasma and liver total cholesterol (TC), triglycerides (TG) levels were also markedly elevated; Lipin1 expression at both mRNA and protein levels were significantly deceased. Compared with CO group, the mRNA and protein levels of AMPKα1 and AMPKα2 were not changed, whereas the p-AMPK (Thr-172) and p-AKT (ser473) levels in liver were significantly decreased in HF group.These findings indicated that the decrease in lipin1 expression and AMPKα activation may contribute to hepatic insulin resistance in diet-induced obese rats.
Keywords: hepatic Insulin resistance; AMP-activated protein kinase; lipin1; Lpin1